2007
DOI: 10.4049/jimmunol.178.9.5762
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Activation and Proliferation Characteristic for HIV-Nef Transgenic Mice Is Lymphopenia Induced

Abstract: The HIV-Nef protein has been implicated in generating high viral loads and T cell activation. Transgenic (tg) mice with constitutive T cell-specific Nef expression show a dramatic reduction in T cell number and highly increased T cell turnover. Previous studies in Nef tg mice attributed this T cell activation to a direct effect of Nef at the cellular level. Given the strongly reduced peripheral T cell numbers, we examined whether this enhanced T cell division might instead be lymphopenia induced. Adoptively tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
2
2
1
Order By: Relevance
“…These results contrast with the study by Koenen and coworkers, who reported no T-cell activation in similar mixed chimeric mice reconstituted with BM cells from wild-type and CD2/Nef Tg mice, expressing Nef in both CD4 and CD8 T cells (26). However, in these latter chimeras, the Nef Tg T cells constituted only 1 to 2% of the total peripheral LN T-cell compartment where activation was measured (26). Moreover, the authors did not document that these residual pLN Tg T cells expressed Nef.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results contrast with the study by Koenen and coworkers, who reported no T-cell activation in similar mixed chimeric mice reconstituted with BM cells from wild-type and CD2/Nef Tg mice, expressing Nef in both CD4 and CD8 T cells (26). However, in these latter chimeras, the Nef Tg T cells constituted only 1 to 2% of the total peripheral LN T-cell compartment where activation was measured (26). Moreover, the authors did not document that these residual pLN Tg T cells expressed Nef.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with this latter scenario, we reported that in CD4C/HIV Nef Tg mice the extent of T-cell activation correlates with levels of Nef expression in CD4 ϩ T cells, thus suggesting a direct involvement of Nef in this activation (53). In contrast, Koenen and coworkers reported that T-cell activation in CD2/Nef Tg mice is induced indirectly by lymphophenia (26). In that study, chimeric mice, which were generated from a mixture of non-Tg and Nef Tg bone marrow (BM) cells, were not lymphopenic, and the donor-derived Nef-expressing Tg T cells did not show an activated phenotype.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…These results show that when Nef is expressed under the regulation of the mCD4, CD4E, or CD4F sequences, thymic and peripheral CD4 ϩ T cells are severely depleted to a degree comparable to that observed in CD4C/HIV Nef Tg mice, confirming previous studies in Tg mice expressing Nef with different T-cell-specific promoters (12,65,89 (58,65,89). FACS analysis showed that a larger proportion of Tg CD4 ϩ T cells expressed CD69 and CD25 cell surface markers and were CD44 high , CD45RB low , and CD62L low cells (Fig.…”
Section: Construction Of Tg Micesupporting
confidence: 89%